Ventilation and air conditioning design approach based on ASHRAE psychrometric chart and Mollier diagram - Lešinskis, Arturs; Strauts, Uldis; Metāls, Mārtiņš; Millers, Renārs; Afoņičevs, Viktors (Frontiers in Built Environment, 2024)
Society needs long-term sustainability and healthy building projects, and indoor air quality assurance engineering systems play a pivotal role in the energy performance of buildings. Therefore, when designing heating, ventilation, and air conditioning systems, it is crucial to make the most technically sound decisions in terms of energy consumption and assess their impact on the building's energy performance. This article delves into the design of ventilation and air conditioning systems, presenting a method for evaluating their performance. The foundation of project development is an agreement on the design criteria, which are developed based on a preliminary analysis of the building concept. This agreement ensures cohesive collaboration among all stakeholders: the client, the architect, the system designer, the contractor, and ultimately the personnel responsible for commissioning, operating, and maintaining the systems post-construction. We suggest conducting a comprehensive analysis of the processes occurring within the space without initially linking them to room air exchange. From this analysis, we derive the angular coefficient for the direction of the air condition change on both a psychrometric chart and a Mollier diagram. The process line on the psychrometric chart provides insights into how the performance factor of the air distribution system will influence the desired supply air parameters. We can then evaluate how significantly the gap between the supply air and the exhaust air parameters expands if the room's air exchange volume is reduced for budgetary reasons. The article showcases this design methodology using a simplified case study.